2010
DOI: 10.1007/s10549-010-0928-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of response to mTOR inhibitor everolimus in pre-operatively treated post-menopausal women with oestrogen receptor-positive breast cancer

Abstract: There is growing evidence that uncontrolled activation of the PI3K/Akt/mTOR pathway contributes to the development and progression of breast cancer. Inhibition of this pathway has antitumour effects in preclinical studies and efficacy in combination with other agents in breast cancer patients. The aim of this study is to characterise the effects of pre-operative everolimus treatment in primary breast cancer patients and to identify potential molecular predictors of response. Twenty-seven patients with oestroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 51 publications
4
52
0
Order By: Relevance
“…In addition to combining them with chemotherapy, hormonal, and antiHER-2 treatments, some preclinical studies have found synergic effect when added to IGF1R or MEK inhibitors, due to their feedback upregulation of the PI3K/Akt pathway [82][83][84][85][86]. On the other hand, some studies have also started to test predictive factors to PI3K inhibitors in order to find more sensitive BC subpopulations, but the results are insufficient to make conclusions [58, 84,[87][88][89][90][91][92][93][94][95].…”
Section: Pi3k/akt Pathway Implication In Breast Cancer Treatmentmentioning
confidence: 99%
“…In addition to combining them with chemotherapy, hormonal, and antiHER-2 treatments, some preclinical studies have found synergic effect when added to IGF1R or MEK inhibitors, due to their feedback upregulation of the PI3K/Akt pathway [82][83][84][85][86]. On the other hand, some studies have also started to test predictive factors to PI3K inhibitors in order to find more sensitive BC subpopulations, but the results are insufficient to make conclusions [58, 84,[87][88][89][90][91][92][93][94][95].…”
Section: Pi3k/akt Pathway Implication In Breast Cancer Treatmentmentioning
confidence: 99%
“…There were 16 studies evaluating everolimus (1492 patients, 17 articles; one study was described in two distinct articles [22,24]) [10,12,13,15,17,[20][21][22][23][24][25][26][27][28][31][32][33]. Ten studies described the results of phase I trials [13,17,[20][21][22][23]27,28,31,32], one described those of a phase I/II trial [15], four studies involved a phase II design [10,25,26,33] and one study involved a phase III design [12].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were conducted on hormone receptor (HR) positive metastatic breast cancer patients [10,12,28], and three studies were conducted in a HER2-positive metastatic setting [15,20,21], while in six studies the distinction between subtypes of breast cancer patients was not made [13,17,25,27,31,32]. None of the studies reported results regarding OS [10,12,13,15,17,[20][21][22][23][24][25][26][27][28][31][32][33]. All studies reported detailed outcomes pertaining to efficacy and/or safety [10,12,13,15,17,[20][21][22][23][24][25][26][27][28][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work attempting to identify predictors of response following single-agent everolimus treatment noted gene expression changes in responding vs. resistant tumors, but no clear-cut pattern was observed. 74 S6K1 as a marker of sensitivity to mTORC1 inhibitors. mTOR inhibition was observed to result in the reversal of resistance in a breast cancer cell line rendered cross-resistant to tamoxifen and fulvestrant, accompanied by reduction in ERα phosphorylated on Ser167.…”
Section: S6k1 In Er-positivementioning
confidence: 99%